Experiências em física em contexto pandêmico : entre dimensões narrativas de autoformação docente e de alfabetização científica e tecnológica dos estudantes - Rodrigues-Moura, Sebastião (2022)
In the current socio-political conjuncture that we are experiencing, the attitude of students in society in defense of science has become imperative, as a legitimate appropriation of their life histories by valuing scientific knowledge. These propositions put me in a privileged scenario as a physics teacher that justify my practice and corroborate the formation of autonomous and critical subjects, capable of transforming their knowledge into practices, in a changing world. This potential movement to emanate youth protagonism in research activities in the period of Basic Education, specifically in Integrated High School in the federal education network, it raises students to narrate their experiences when (re)count tell their experiences in a social context experienced during the covid-19 pandemic, which led me to question: In what terms are the pedagogical experiences in Physics, developed in a collaborative space in the period of the pandemic, for the process of transformation of the teaching practice itself to the time in which they provide the scientific and technological literacy of students? With a view to this compass that guides doctoral research, through Teaching through Research (TTR), I agree to understand how pedagogical experiences in Physics are constituted, developed in a collaborative space in the period of the pandemic, for the process of transformation of the teaching practice itself and for the promotion of student scientific and technological literacy. I take Narrative Inquiry as a research method and as a phenomenon to be investigated to understand the experiences of students in scientific activities of virtual classroom, of formative experiences collective and individual, considered fundamental to contextualize a cloud of experiences in the autoformative dimension and to the reflective look on pedagogical practice. In the coming and going of narratives, I move under a detailed look at Discursive Textual Analysis (DTA), to understand the lived experiences and evidence for Scientific and Technological Literacy (STL) constituted by students. From this analytical movement in the three-dimensional space of the cloud of experiences emerge three axes that contextualize the investigative scenario: 1) Arc of narratives: a walk towards my practice in narratives constituting the becoming a physics teacher in ancient times; 1) Cycle of narratives: (re)visiting experiences in Physics and understanding scientific education; and, 3) Narrative flow: between research and STL, analyzing indicators in times of remote teaching. From the analysis of the results emerge dimensions that point to the limits, possibilities, existences and resistances about my self-formation because it is a space of proper investigation of training as a drive for changes in teaching action, in which I create favorable conditions for knowledge about pedagogical action, reconstructing and recognizing formative opportunities for the renewal of physics teaching, enabling transformations necessary for the scientific learning of students, while I make a critical reflection when I become aware of the very limits of remote teaching. Furthermore, I note that the appropriation of scientific knowledge associated with the concepts of the pandemic period mobilized knowledge necessary to promote changes on scientific education and citizen education of students, become autonomous and protagonists of scientific research, which enables an action for changes of thought, understandings about the nature of science and its implications in social practices in remote education, as well as providing a collaborative sense of learning, scientific culture and conscious decision-making for life in society, through STL. This scientific evidence confirms the thesis that I argue that pedagogical experiences in physics during the pandemic, through remote teaching characterized by collaborative practices, constitute clouds of experiences that confluate the movement of transformation of the teaching practice itself for citizen education and evidence indicators of the STL of students.